External networks and institutional idiosyncrasies: the Common Security and Defence Policy and UNSCR 1325 on women, peace and security. Issue 1 (2nd January 2017) - Joachim, Jutta; Schneiker, Andrea; Jenichen, Anne
Abstract: In 2008, the Council of the European Union (EU) adopted a 'Comprehensive Approach' that outlines a strategy for securing gender mainstreaming; two years later, the Council introduced a set of indicators to assess its implementation. The EU was responding to the United Nations Security Council's call for regional institutions to assist in implementing Security Council Resolution (UNSCR) 1325, adopted on 31 October 2000, concerning 'women, peace and security'. This resolution sought to meet the 'urgent need to mainstream a gender perspective into peacekeeping operations'. Considering that prior exposure to gender issues, resources and well-established relations with civil society and gender advocates are lacking, the adoption of both the Comprehensive Approach and the indicators, as well as the structures and procedures established since then as part of the EU's Common Security and Defence Policy, requires some explanation. This article draws on feminist institutionalist approaches to argue that the impetus for change came from individuals and groups within the EU who were involved in external networks, both above and below the supranational level, who seized on institutional idiosyncrasies that also shaped the implementation of UNSCR 1325 in important ways.